Supply Chain Adaptation of Finnish Companies in Chinese Institutional Environment - Hämäläinen, Joonas (My University, 2016)
Within the last few decades of operations and supply chain management, the field has seen the rise of so called best practices, methods that will help supply chains obtain their business goals and gain a competitive edge. These methods were thought to be universal. This however is not always the case, as the surrounding business environment could have a significant impact on what will be effective in gaining competitive edge. Contingency theory states that the success of a supply chain is determined by both internal capabilities, as well as external context aligning. This creates a strategic fit, which is a major determinant of success. In order for supply chains to reach this strategic fit, they must adapt. As China has seen rapid growth and over the last few decades become one of the major economies of the world, Western companies have tried to establish themselves there, only to find that the Chinese market is extremely difficult to operate in. The aim of this thesis was to investigate from contingency theory perspective, what are the institutional factors that affect supply chain management of Finnish companies operating in China, and how do Finnish companies adapt their supply chains to better fit the Chinese institutional environment. A theoretical model was created for this thesis, in which supply chains possess resources, which can be combined in a meaningful manner to create capabilities. Both resources and capabilities are affected by the surrounding institutional environment, which forces supply chains to adapt in order to find a better strategic fit. A total of six Finnish managers from three large and three small companies operating in China were interviewed. The results indicated that the Chinese business environment is significantly different, than that of Finland or Western countries in general. Three institutional factors were identified: Confucian though, fast-paced business environment, and managing labor force. These three institutional factors made the relationship and delivery capabilities particularly important, as well as human resources, reputation, physical resources and technological resources. In conclusion, it was discovered that the Chinese institutional environment is heavily affected by Confucian thought, as well as the rapid market growth. These are the two most important institutional factors that shape the Chinese market. If supply chains wish to be successful in China, adaptation regarding these two institutional factors should yield good results.